A fast gelling agent and its preparation method and application
By combining fast gelling agent with graded gravel to form an organic flexible polymerization consolidation layer, the problem of poor treatment effect of slurry and mud in the existing technology of basin railway roadbeds is solved, and the effects of high strength, anti-seepage, anti-aging and rapid construction of the surface layer of the roadbed bed are achieved.
Patent Information
- Application Number
- CN202411876002.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-04
AI Technical Summary
The existing treatment plans for treating diseases such as slurry and mud on the basin railway roadbed are poor in general, have average effects, high engineering cost, and are difficult to cure repeatedly, especially under train vibration loads.
It provides a fast gelling agent, which is sprayed to the surface of the roadbed base bed by using a gear pump and an air compressor by using a gear pump and an air compressor, and forms an organic flexible polymerization consolidation layer with manual laying, which has the advantages of high early strength, uneven dynamic load resistance, anti-seepage, anti-aging, and anti-freeze-thaw.
It significantly improves the ability of the basin railway roadbed to protect the rainwater seepage to form slurry and mud, and enhances the overall strength, density and uniformity of the surface layer of the roadbed bed, and is simple to construct and high operating efficiency, meeting the needs of large-scale rapid construction and strength recovery of existing linebeds.
Smart Images

Figure CN119752204A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials for railway roadbed maintenance and repair, and in particular to a fast gelling agent and a preparation method and application thereof. Background Art
[0002] In newly built and operated ballasted railways, the roadbed subgrade is the direct carrier of train vibration loads, which directly affects the safety of railway operations. In addition to some existing ballasted railways in my country that use graded crushed stone or graded crushed stone mixed with cement as the subgrade surface layer of the subgrade structure, most of them use high-quality A and B group fillers to fill the subgrade. In fact, due to the lack of high-quality fillers and other reasons, the subgrade fillers do not meet the requirements of the specifications for many sections. The combined effects of atmospheric precipitation infiltration and train vibration loads will cause the subgrade rock and soil of the subgrade with poor fillers to deteriorate, resulting in subgrade subsidence, mud bubbling, ballast bags, ballast grooves and other subgrade diseases, which are called the "cancer" of railway subgrade regulation and pose a huge risk to railway operation safety.
[0003] At present, the treatment of ballasted railway subgrade diseases such as mud and slurry is mostly carried out by full-throw paving, replacement of high-quality fillers, grouting (organic and inorganic), subgrade drainage and other solutions, but the universality is poor and the effects are generally mediocre. The main problems are: first, due to the effect of the train vibration load, the ballast constantly impacts and squeezes the sealing layer, while the strength of the full-throw paving is generally low, and the puncture resistance is weak. After a few years, it will be squeezed and cracked, and the water-blocking effect will be lost, resulting in a short effective period of the sealing layer; second, the subgrade diseases such as mud and slurry of the roadbed are mainly caused by the special rock and soil effects of the roadbed filler. Local replacement of high-quality fillers may be effective in the short term, but over time, mud and slurry will reappear. The short effective period of treatment causes repeated construction and increases the project cost; third, the grouting (organic and inorganic) slurry diffuses unevenly and has poor integrity, and a complete and stable sealing layer cannot be formed. The grouting solidification time is long, and the rigid base formed later is very easy to be squeezed and cracked under the vibration load of the train, resulting in failure; fourth, the subgrade drainage method is simple, but the areas where mud and slurry occur are often difficult to drain, and the rain infiltration of the roadbed is also difficult to avoid, resulting in limited effect of this method. In addition, due to the strict management of railway operations and special on-site operating conditions, the existing solutions for controlling slurry and mud are difficult to meet the special working conditions of rapid construction and strength recovery of existing linebeds on a large scale.
[0004] Sealing the surface of the subgrade and blocking the infiltration of atmospheric precipitation, high-strength flexible sealing materials are the key to solving the mud bubbling of existing railway subgrades. Subgrade sealing is to lay a sealing layer (waterproof layer) on the surface of the subgrade to prevent surface water from infiltrating and softening the subgrade soil, and to prevent the mud generated by mud bubbling from surging to the surface of the roadbed. At the same time, it can also improve the bearing capacity of the subgrade surface to a certain extent. As a typical viscoelastic material, polymer stone chip mixture has the advantages of vibration reduction, noise reduction, adaptability to subgrade deformation, easy maintenance, environmental protection and recyclability. It is a very suitable material for railway subgrade sealing layer. Polymer stone chip mixture refers to a material formed by bonding aggregates (graded crushed stone) together with asphalt as a gelling agent, and its strength is determined by the aggregates and gelling agents. Summary of the invention
[0005] In view of the problems that the full-cast paving, high-quality filler replacement, grouting (organic, inorganic), base bed drainage and other roadbed mud and mud treatment solutions proposed in the above background technology have poor effects, high engineering costs, repeated construction, and are difficult to cure, the present invention provides a fast gel coagulant material, which is liquid in a sealed state at room temperature, has a condensation temperature of -20°C, a softening point greater than ≥60°C, has good ductility and viscosity at room temperature, strong fluidity, short solidification time (≤2h, 25°C), high initial strength, strong toughness, and has the advantages of convenient transportation and simple construction. The material is mixed with graded crushed stone at room temperature in a certain proportion, and a gear pump and an air compressor are used to spray the sealing material from the line through a material pipe to the surface of the roadbed base bed. The material can be quickly condensed to form an organic flexible polymer consolidation layer in combination with the artificial laying of a fast gel coagulant anti-seepage patch, which has the advantages of high early strength, good resistance to uneven dynamic load bending, no cracking, impermeability, aging resistance, and freeze-thaw resistance.
[0006] The technical solution of the present invention is as follows:
[0007] In the first aspect, the present invention provides a fast gelling agent, comprising the following raw materials in parts by weight: 42-48 parts of gelling agent base asphalt, 20-35 parts of diluent, 5-10 parts of asphalt modifier, 0.1-0.5 parts of stabilizer, 0.2-1 parts of asphalt anti-stripping agent, 2-6 parts of asphalt plasticizer, 0.2-0.6 parts of anti-aging agent, 4-7 parts of rock asphalt powder, 0.04-0.08 parts of graphene, and 0.5-1 parts of nano calcium carbonate powder.
[0008] Furthermore, the diluent is gasoline and / or diesel, the asphalt modifier is any one or more of styrene-butadiene-styrene terpolymer, styrene-butadiene copolymer, and polychloroprene, the stabilizer is benzenesulfonic acid and / or phenylboric acid, the asphalt anti-stripping agent is an amine asphalt anti-stripping agent or a non-amine asphalt anti-stripping agent, the asphalt plasticizer is dibutyl phthalate and / or trioctyl trimellitate, and the anti-aging agent is montmorillonite or organic montmorillonite.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned rapid gelling agent, comprising the following steps:
[0010] S1: heating the gelling agent base asphalt to a molten state, adding an asphalt modifier, an asphalt anti-stripping agent, a stabilizer, and a diluent thereto in sequence, and stirring at a high speed to obtain a first mixture;
[0011] S2: When the temperature of the first mixture drops to 70-90° C., adding asphalt plasticizer and anti-aging agent thereto, and stirring evenly to obtain a second mixture;
[0012] S3: The second mixture is allowed to stand for 12-14 hours, and then rock asphalt powder, graphene and nano calcium carbonate powder are added thereto, and the mixture is quickly stirred and sealed to obtain the fast gelling agent.
[0013] Furthermore, in step S1, the stirring speed of high-speed stirring is 3000-5000 r / min, and the stirring time is 25-35 min; in step S2, the stirring speed of stirring is 1500-2500 r / min, and the stirring time is 25-35 min; in step S3, the stirring speed of rapid stirring is 2000-4000 r / min, and the stirring time is 15-25 min.
[0014] In a third aspect, the present invention provides the use of the above-mentioned fast gelling agent in the closed construction of ballasted track subgrade.
[0015] Furthermore, the fast gel coagulant and graded crushed stone are quickly sprayed onto the surface of the roadbed through a material pipe and an air compressor at room temperature, and the fast gel coagulant anti-seepage sticker is manually laid on the ballasted track roadbed to form an organic flexible polymer consolidation layer. The addition amount of the fast gel coagulant accounts for 9-12% of the weight of the graded crushed stone. The maximum particle size of the graded crushed stone is 13.2 mm, and the nominal maximum particle size is 9.5 mm. The fast gel coagulant anti-seepage sticker is made of the fast gel coagulant and glass fiber, and has a thickness of 2-3 mm.
[0016] Furthermore, the grading range of the graded crushed stone is: particle size <0.075mm accounts for 4.2-7.2%, particle size <0.15mm accounts for 6.8-14.8%, particle size <0.3mm accounts for 9.8-20.6%, particle size <0.6mm accounts for 13.6-29.5%, particle size <1.18mm accounts for 22.7-40.6%, particle size <2.36mm accounts for 32.1-55.2%, particle size <4.75mm accounts for 52.7-74.6%, particle size <9.5mm accounts for 92.6-97.8%, and particle size <13.2mm accounts for 100%.
[0017] Furthermore, the grading range of the graded gravel is: particle size <0.075mm accounts for 7.2%, particle size <0.15mm accounts for 14.8%, particle size <0.3mm accounts for 20.6%, particle size <0.6mm accounts for 29.5%, particle size <1.18mm accounts for 40.6%, particle size <2.36mm accounts for 55.2%, particle size <4.75mm accounts for 74.6%, particle size <9.5mm accounts for 97.8%, and particle size <13.2mm accounts for 100%; the added amount of the fast gelling agent accounts for 9.5% of the weight of the graded gravel.
[0018] Furthermore, the thickness of the organic flexible polymer consolidation layer is 3-5 cm.
[0019] The beneficial effects of the present invention are:
[0020] (1) The fast gel coagulant provided by the present invention is liquid in a sealed state at room temperature, has a condensation temperature of -20°C, a softening point greater than or equal to 60°C, has good ductility and viscosity at room temperature, strong fluidity, short solidification time (≤2h, 25°C), high initial strength, strong toughness, etc.
[0021] (2) The fast gelling agent provided by the present invention is mixed with graded crushed stone in a certain proportion at room temperature, and a gear pump and an air compressor are used to spray the sealing material evenly onto the surface of the roadbed through a material pipe from below the line. Combined with the artificial laying of the fast gelling agent anti-seepage patch, it can quickly condense to form an organic flexible polymer consolidation layer. The consolidation layer has a dense and stable structure, high early strength, high overall strength and good anti-seepage performance, and has high flexibility, bending resistance and ballast puncture resistance under the action of train vibration load.
[0022] (3) The present invention applies the above-mentioned fast gelling agent to the closed construction of ballasted track subgrade, which significantly improves the ability of the ballasted railway subgrade to protect against various subgrade diseases such as mud bubbling, subsidence, ballast bags, and ballast grooves caused by rainwater infiltration. On the basis of good anti-seepage ability, the overall strength, density and uniformity of the subgrade surface are improved. The construction method is simple and the operation efficiency is high, which can meet the special working conditions of large-scale rapid construction and strength recovery of existing line subgrades. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0024] Figure 1is a curve diagram showing the change of stability with the amount of gelling agent in a Marshall stability test in a specific embodiment;
[0025] Figure 2 is a curve diagram showing the change of the gross volume relative density with the amount of gelling agent in a volume parameter test in a specific embodiment;
[0026] Figure 3 is a curve diagram showing the variation of the theoretical maximum relative density with the amount of gelling agent in a volume parameter test in a specific embodiment;
[0027] Figure 4 It is a curve diagram showing the change of void ratio with the amount of gelling agent in the volume parameter test in a specific embodiment. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0029] In the first aspect, the present invention provides a fast gelling agent, comprising the following raw materials in parts by weight: 42-48 parts of gelling agent base asphalt, 20-35 parts of diluent, 5-10 parts of asphalt modifier, 0.1-0.5 parts of stabilizer, 0.2-1 parts of asphalt anti-stripping agent, 2-6 parts of asphalt plasticizer, 0.2-0.6 parts of anti-aging agent, 4-7 parts of rock asphalt powder, 0.04-0.08 parts of graphene, and 0.5-1 parts of nano calcium carbonate powder.
[0030] In the present invention, the fast gel coagulant is composed of multi-phase materials, each of which has obvious differences in chemical composition, structure and properties, making the interface interaction and adhesion mechanism between the coagulant and the aggregate more complex, and can enhance the adhesion performance of the interface between the coagulant and the aggregate, improve the road performance of the consolidation layer formed after the coagulant and the aggregate are mixed, and extend the service life of the consolidation layer. The constructed consolidation layer can form a good protective layer on the surface of the roadbed, improve the overall strength and uniformity of the upper part of the roadbed, isolate the infiltration of atmospheric precipitation, and prevent various roadbed diseases caused by the softening and moistening of the bed due to the infiltration of rainwater. At the same time, the fast gel coagulant provided by the present invention has a short setting time and can quickly develop strength after mixing with aggregate.
[0031] In addition, in the present invention, the rock asphalt powder is the powder of natural rock asphalt. Natural rock asphalt is natural asphalt formed by petroleum penetrating into rock under the action of long-term natural factors. It has a large molecular weight and strong activity. The functional groups formed by its nitrogen, oxygen, sulfur and other elements are generally higher than those of matrix asphalt (petroleum asphalt). It has high strength, aging resistance, durability, adhesion to aggregates and anti-peeling properties, and it has good compatibility with matrix asphalt. Therefore, adding rock asphalt to asphalt-based gelling agent can greatly improve the initial strength and durability of the asphalt-based gelling agent.
[0032] The graphene, as a nano-carbon material, is in the form of flaky particles with a special honeycomb lattice structure. It has the advantages of high strength, high toughness, large specific surface area and high surface activity. It is easily adsorbed on the surface of fine stone particles, forming multiple physical cross-linking points between the stone particles and the gelling agent, thereby improving the overall structure of the mixture, enhancing the connection area and adhesion strength between the gelling material and the crushed stone particles and asphalt plasticizer. The special flaky structure is oriented and arranged, which enhances the overall anti-permeability performance of the consolidated layer.
[0033] The nano calcium carbonate powder can reduce the microscopic voids in the consolidation layer, and can form a tight combination with graphene and fine stone chips under the condition of the surrounding medium, blocking the microstructural channels of the seepage water, enhancing the impermeability, and improving the uniformity of the overall strength and anti-aging properties.
[0034] In a specific embodiment, the diluent is gasoline and / or diesel, the asphalt modifier is any one or more of styrene-butadiene-styrene terpolymer (SBS), styrene-butadiene copolymer (SIS), polychloroprene (CR), the stabilizer is benzenesulfonic acid and / or phenylboric acid, the asphalt anti-stripping agent is an amine asphalt anti-stripping agent or a non-amine asphalt anti-stripping agent, the asphalt plasticizer is dibutyl phthalate (DBP) and / or trioctyl trimellitate (TOTM), and the anti-aging agent is montmorillonite or organic montmorillonite.
[0035] In the above embodiments, the styrene-butadiene-styrene terpolymer can significantly improve the high and low temperature performance, elasticity, cohesive adhesion performance, and stability and anti-aging performance of the mixture of asphalt. The styrene-butadiene copolymer is a thermoplastic elastomer made by anionic polymerization of styrene and isoprene, and has better performance than SBS. The polychloroprene has the characteristics of high initial adhesion and high bonding strength.
[0036] It should be noted that the diluent is to provide fluidity to the gelling agent base asphalt; the stabilizer is to ensure the stability of the gelling agent emulsion; the asphalt anti-stripping agent is to improve the adhesion between asphalt and aggregate; the asphalt plasticizer is to increase the plastic deformation capacity of asphalt and improve its low temperature performance; the anti-aging agent is to improve the antioxidant stability and thermal stability of asphalt. The specific agent types of each agent in the above embodiments are only the preferred agent types of the present invention, and other agent types that can achieve the same purpose can also be applied to the present invention.
[0037] In a second aspect, the present invention provides a method for preparing the above-mentioned rapid gelling agent, comprising the following steps:
[0038] S1: heating the gelling agent base asphalt to a molten state, adding an asphalt modifier, an asphalt anti-stripping agent, a stabilizer, and a diluent thereto in sequence, and stirring at a high speed to obtain a first mixture;
[0039] S2: When the temperature of the first mixture drops to 70-90° C., adding asphalt plasticizer and anti-aging agent thereto, and stirring evenly to obtain a second mixture;
[0040] S3: The second mixture is allowed to stand for 12-14 hours, and then rock asphalt powder, graphene and nano calcium carbonate powder are added thereto, and the mixture is quickly stirred and sealed to obtain the fast gelling agent.
[0041] In a specific embodiment, in step S1, the stirring speed of high-speed stirring is 3000-5000 r / min, and the stirring time is 25-35 min; in step S2, the stirring speed of stirring is 1500-2500 r / min, and the stirring time is 25-35 min; in step S3, the stirring speed of rapid stirring is 2000-4000 r / min, and the stirring time is 15-25 min.
[0042] In the above embodiment, through the preparation method, the various raw materials in the rapid gelling agent of the present invention can be fused and cross-linked together to form a stable emulsion liquid material.
[0043] In a third aspect, the present invention provides the use of the above-mentioned fast gelling agent in the closed construction of ballasted track subgrade.
[0044] In a specific embodiment, the fast gel coagulant and graded crushed stone are quickly sprayed onto the surface of the roadbed through a material pipe from the line using a gear pump and an air compressor at room temperature, and the fast gel coagulant anti-seepage sticker is manually laid on the ballasted track roadbed to form an organic flexible polymer consolidation layer. The addition amount of the fast gel coagulant accounts for 9-12% of the weight of the graded crushed stone. The maximum particle size of the graded crushed stone is 13.2 mm, and the nominal maximum particle size is 9.5 mm. The fast gel coagulant anti-seepage sticker is made of the fast gel coagulant and glass fiber, and has a thickness of 2-3 mm.
[0045] In the above embodiment, the organic flexible polymer consolidation layer can be waterproof, which has high requirements for porosity and also needs to ensure a certain strength to prevent it from cracking under the train load. By designing the addition amount of the fast gelling agent to be 9-12% of the weight of the graded crushed stone, the mixture can be guaranteed to have a high stability. By setting the nominal maximum particle size to 9.5 mm, the waterproof performance of the mixture can be the best.
[0046] In a specific embodiment, the grading range of the graded crushed stone is: particle size <0.075mm accounts for 4.2-7.2%, particle size <0.15mm accounts for 6.8-14.8%, particle size <0.3mm accounts for 9.8-20.6%, particle size <0.6mm accounts for 13.6-29.5%, particle size <1.18mm accounts for 22.7-40.6%, particle size <2.36mm accounts for 32.1-55.2%, particle size <4.75mm accounts for 52.7-74.6%, particle size <9.5mm accounts for 92.6-97.8%, and particle size <13.2mm accounts for 100%.
[0047] In a specific embodiment, the gradation range of the graded crushed stone is: particle size <0.075mm accounts for 7.2%, particle size <0.15mm accounts for 14.8%, particle size <0.3mm accounts for 20.6%, particle size <0.6mm accounts for 29.5%, particle size <1.18mm accounts for 40.6%, particle size <2.36mm accounts for 55.2%, particle size <4.75mm accounts for 74.6%, particle size <9.5mm accounts for 97.8%, particle size <13.2mm accounts for 100%; the addition amount of the fast gel coagulant accounts for 9.5% of the weight of the graded crushed stone. In this embodiment, the gradation range of the graded crushed stone and the amount of the fast gel coagulant are the optimal proportions, which can ensure that the organic flexible polymer consolidation layer has the lowest porosity and the highest stability.
[0048] In a specific embodiment, the thickness of the organic flexible polymer consolidation layer is 3-5 cm.
[0049] Example
[0050] A fast gelling agent is prepared by the following steps:
[0051] (1) heating the gelling agent base asphalt to 170° C. to make it molten, adding the asphalt modifier, asphalt anti-stripping agent, stabilizer, and diluent thereto in sequence, and stirring at a speed of 4000 r / min for 30 min to obtain a first mixture;
[0052] (2) when the temperature of the first mixture drops to 80° C., adding asphalt plasticizer and anti-aging agent thereto, and stirring at a speed of 2000 r / min for 30 min to obtain a second mixture;
[0053] (3) The second mixture was allowed to stand for 12 hours, and then rock asphalt powder, graphene and nano calcium carbonate powder were added thereto. The mixture was stirred at a speed of 3000 r / min for 20 minutes and then sealed and packaged to obtain the fast gelling agent.
[0054] In this embodiment, the formula of the rapid gelling agent is shown in Table 1:
[0055] Table 1 Formula of fast gelling agent (unit, g)
[0056]
[0057]
[0058] Comparative Example 1
[0059] Different from Example 1, the rock asphalt powder, graphene and nano calcium carbonate powder are not added in this comparative example.
[0060] Comparative Example 2
[0061] Different from Example 1, the graphene and the nano calcium carbonate powder are not added in this comparative example.
[0062] Comparative Example 3
[0063] Different from Example 1, the rock asphalt powder and the nano calcium carbonate powder are not added in this comparative example.
[0064] Comparative Example 4
[0065] Different from Example 1, the rock asphalt powder and the graphene are not added in this comparative example.
[0066] Comparative Example 5
[0067] Different from Example 1, the rock asphalt powder is not added in this comparative example.
[0068] Comparative Example 6
[0069] Different from Example 1, the graphene is not added in this comparative example.
[0070] Comparative Example 7
[0071] Different from Example 1, the nano calcium carbonate powder is not added in this comparative example.
[0072] With reference to the test method in the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011) for asphalt materials, the main technical indicators of the fast gelling agents prepared in each embodiment of the present invention and the common gelling agents prepared in each comparative example were measured, and the results are shown in Table 2 and Table 3:
[0073] Table 2 Main technical indicators of the fast gelling agent of the present invention
[0074]
[0075] Table 3 Main technical indicators of common gelling agents in comparative examples
[0076]
[0077] In Table 2 and Table 3, the penetration index is used to reflect the temperature sensitivity of the cementitious material, the ductility is used to reflect the plasticity of the material, the softening point can evaluate the heat resistance of the material, and the rotational viscosity reflects the construction and workability of the cementitious material.
[0078] As can be seen from Table 2, the various indicators of the rapid gelling agents prepared in Examples 1 to 3 meet the requirements of the specifications, and their temperature sensitivity is low, their properties are less affected by temperature changes, and their overall stability is high. At the same time, they also have good plasticity, and after being bonded with graded crushed stone, they are not prone to breakage or cracks under the action of external tension; the softening point is high, up to 86.5°C, and for the sealing layer on the subgrade soil under the ballast, its temperature generally does not exceed 25°C, so the rapid gelling agents prepared in Examples 1 to 3 are fully satisfied when used in the sealing layer. High temperature resistance requirements. At the same time, the rapid gelling agent of the present invention is a diluted flowing liquid when it is mixed at room temperature, and has good workability and is easy to mix during construction.
[0079] By comparing Table 2 and Table 3, it can be seen that adding only one or two of the three components of rock asphalt powder, graphene and nano calcium carbonate powder cannot achieve the technical effect that can be achieved by the present invention.
[0080] The fast gelling agent of the present invention is used in combination with aggregate (graded crushed stone) to be applied to the closed construction of the subgrade of ballasted track. When used, the mixing ratio of the fast gelling agent and the aggregate (graded crushed stone) is designed as follows:
[0081] The main function of the polymer sealing layer is waterproofing, and it has high requirements for the porosity. At the same time, it is also necessary to ensure a certain strength to prevent it from cracking under the train load. According to relevant research, asphalt mixtures with a nominal maximum particle size of 9.5mm have better waterproofing performance. Therefore, this polymer mixture mix design uses a dense gradation with a nominal maximum particle size of 9.5mm for testing, and the corresponding asphalt mixture type is AC-10. Within the gradation range, by reasonably adjusting the aggregate blending ratio, three gradations are designed near the upper limit, median, and lower limit of the AC-10 gradation range as test gradations, and are named AC-10S, AC-10Z, and AC-10X, respectively, as shown in Table 4 below:
[0082] Table 4 Aggregate design gradation of polymer mixture
[0083]
[0084] The fast gelling agent prepared in Example 1 was used as the binder of the polymer mixture, and five groups of different gelling agent dosages were set, with the dosage interval of 0.5%, namely 8%, 8.5%, 9%, 9.5%, and 10%. Marshall stability tests and volume parameter tests were performed on polymer flexible mixtures with different mix ratios to obtain the optimal mix ratio of gelling agent and graded mineral material.
[0085] In the Marshall stability test, the stability MS changes with the amount of gelling agent as follows Figure 1 As shown. Figure 1 It can be seen that the Marshall stability MS of the mixtures of the three design gradations AC-10S, AC-10Z and AC-10X at the five dosages of the gelling agent is much greater than the requirement of MS ≥ 8KN in the specification. When the dosage of the gelling material is the same, the stability of the gelling agent mixture of AC-10S gradation is obviously greater than that of the other two gradations.
[0086] The volume parameter test is to measure two volume indicators, namely the gross volume relative density and theoretical maximum relative density of the polymer mixture. The gross volume relative density is obtained by the surface dry method in the "Technical Specifications for Highway Asphalt Pavement Construction" (JTGF40-2017), while the theoretical maximum relative density is calculated using the formula in the "Technical Specifications for Highway Asphalt Pavement Construction" (JTGF40-2017). Based on the two volume indicators (gross volume relative density and theoretical maximum relative density) measured by the volume parameter test, the void ratio of the polymer mixture can be calculated according to the formula in the "Technical Specifications for Highway Asphalt Pavement Construction" (JTGF40-2017).
[0087] The bulk relative density, theoretical maximum relative density and porosity were selected as key volume parameters, and the relationship between the amount of rapid gelling agent and them was plotted. The results are shown in Figure 2. Figure 2-Figure 4 shown.
[0088] from Figure 2 It can be seen that after the amount of gelling agent reaches 8%, the bulk relative density of the mixture of the three design gradations will gradually increase with the increase of the amount, and reach the maximum bulk relative density within the amount range. AC-10S, AC-10Z, and AC-10X mixtures reach the maximum bulk relative density when the amount of gelling agent is 9.5%, 9.0%, and 9.0%, respectively. At this time, the mixture is in the most dense state, and the maximum bulk relative density of the three design gradations is not much different. When the amount of gelling agent continues to exceed this amount, the bulk relative density of the mixture decreases instead. This may be because when there is too much gelling agent, the mixture is "over-oiled", which makes compaction difficult, causing the bulk relative density to decrease instead of increase.
[0089] from Figure 3 It can be seen that the relationship between the theoretical maximum relative density and the amount of gelling agent for the three design graded mixtures is consistent, and the theoretical maximum relative density decreases linearly with the increase of the amount of gelling agent. In the range of 8% to 10% of the gelling agent, the overall decrease is about 2.4%, which shows that the amount of gelling agent has little effect on the theoretical maximum relative density of the mixture.
[0090] from Figure 4 It can be seen that the void ratio of the three designed graded mixtures decreases with the increase of the amount of gelling agent, and the rate of decrease shows a trend of first steep and then slow. The void ratio of AC-10S, AC-10Z, and AC-10X mixtures tends to be stable when the amount of gelling agent is 9.5%, 9.0%, and 9.0%, respectively. Continuing to increase the amount of gelling agent has little effect on reducing the void ratio. The size of the void ratio is crucial to the waterproof ability of the base bed closed waterproof layer. The research results show that when the void ratio is less than 3%, the mixture can basically achieve the effect of impermeability. In this test, the void ratio of the three graded mixtures was above 3% when the amount of gelling agent was 8.0% and 8.5%.
[0091] Taking into account the target functions of the polymer mixture as a base bed sealing layer (waterproof and anti-cracking), with lower porosity and higher stability as the design goals, and referring to the test results of the volume parameter test and the standard Marshall stability test, after comprehensive comparison, it was determined that AC-10S was the optimal grading and 9.5% of the gelling agent was the optimal oil-stone ratio.
[0092] AC-10S graded gravel was selected, and the rapid gelling agent of Example 1 was added in an amount of 9.5% and mixed with the graded gravel to obtain polymer mixture specimen 1; AC-10S graded gravel was selected, and the ordinary gelling agents of Comparative Examples 1 to 7 were added in an amount of 9.5% and mixed with the graded gravel to obtain polymer mixture specimens 2 to 8.
[0093] The specimens 1 to 8 were subjected to the water immersion Marshall test, freeze-thaw splitting test, and anti-aging test in order to test the water damage resistance, low temperature crack resistance, and anti-aging properties of the polymer mixture. The results are shown in Tables 5 to 7:
[0094] Table 5 Immersion Marshall test results
[0095] type Specimen 1 Specimen 2 Specimen 3 Specimen 4 Specimen 5 Specimen 6 Specimen 7 Specimen 8 Standard stability (KN) 30.04 26.95 28.35 26.71 27.53 28.14 28.79 28.87 Water immersion stability (KN) 28.25 25.23 26.39 24.49 25.42 26.30 26.41 26.77 Residual stability after immersion in water (%) 94.04 93.63 93.09 91.68 92.35 93.45 91.75 92.74
[0096] Table 6 Freeze-thaw splitting test results
[0097]
[0098]
[0099] Table 7 Anti-aging test results (comparison of gelling agent indicators before and after aging)
[0100]
[0101]
[0102] The results in Table 5 show that the Marshall stability of specimen 1 after immersion is 94.04%, which is much higher than the requirement of not less than 85% for asphalt mixture in the Technical Specifications for Highway Asphalt Pavement Construction. The results in Table 6 show that the freeze-thaw splitting test strength ratio of specimen 1 is 90.96%, which meets the requirement of not less than 80% in the specification. This proves that specimen 1 has good water stability and excellent water damage resistance, and is less affected by water immersion and freeze-thaw.
[0103] The results in Table 7 show that the main indicators of the fast-gelling material of Example 1 do not change greatly after accelerated aging, which indicates that the anti-aging performance of the fast-gelling material is good, and the polymer mixture with the fast-gelling material as the main component can meet the requirements of long-term use.
[0104] From the results in Tables 5 to 7, it can be seen that compared with specimen 1, specimens 2 to 8 have worse water damage resistance (affected by water immersion and freeze-thaw), low-temperature crack resistance and aging resistance.
[0105] The following compressive strength tests were performed on specimens 1 and 2:
[0106] Compressive strength tests were conducted on specimens 1 and 2 with reference to the Highway Asphalt Pavement Design Specification (JTG D50-2006). A cylindrical specimen was used with a diameter of 101.60 mm. The test instrument was a universal material testing machine, with a maximum load that did not exceed 80% of its range and was not less than 20% of its range. The loading rate was maintained at 2 mm / min. The testing machine had a servo system, and the speed remained basically unchanged during the loading process. The test results are shown in Table 8:
[0107] Table 8 Compressive strength test results
[0108]
[0109] It can be seen from Table 8 that specimen 1 has a shorter setting time than specimen 2, and its initial setting strength and long-term strength are higher than those of specimen 2.
[0110] In summary, the fast-gelling coagulant provided by the present invention and the graded crushed stone are mixed in a certain ratio, and an air compressor is used to spray the sealing material from the line to the surface of the roadbed through a material pipe. After artificially laying the fast-gelling coagulant anti-seepage sticker, it can be directly covered on the surface of the roadbed as a waterproof layer and reinforced structural surface layer of the base bed. It is in close contact with the roadbed body and seamlessly connected, and has good flexible strength, anti-seepage performance and puncture resistance.
[0111] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical contents to make some changes or modifications to the embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A fast gelling agent, characterized in that: The invention comprises the following raw materials in parts by weight: 42-48 parts of gelling agent base asphalt, 20-35 parts of diluent, 5-10 parts of asphalt modifier, 0.1-0.5 parts of stabilizer, 0.2-1 parts of asphalt anti-stripping agent, 2-6 parts of asphalt plasticizer, 0.2-0.6 parts of anti-aging agent, 4-7 parts of rock asphalt powder, 0.04-0.08 parts of graphene and 0.5-1 parts of nano calcium carbonate powder.
2. The rapid gelling agent according to claim 1, characterized in that The diluent is gasoline and / or diesel, the asphalt modifier is any one or more of styrene-butadiene-styrene terpolymer, styrene-butadiene copolymer, and polychloroprene, the stabilizer is benzenesulfonic acid and / or phenylboric acid, the asphalt anti-stripping agent is an amine asphalt anti-stripping agent or a non-amine asphalt anti-stripping agent, the asphalt plasticizer is dibutyl phthalate and / or trioctyl trimellitate, and the anti-aging agent is montmorillonite or organic montmorillonite.
3. The method for preparing the rapid gelling agent according to claim 1 or 2, characterized in that: The following steps are involved: S1: heating the gelling agent base asphalt to a molten state, adding an asphalt modifier, an asphalt anti-stripping agent, a stabilizer, and a diluent thereto in sequence, and stirring at a high speed to obtain a first mixture; S2: When the temperature of the first mixture drops to 70-90° C., adding asphalt plasticizer and anti-aging agent thereto, and stirring evenly to obtain a second mixture; S3: The second mixture is allowed to stand for 12-14 hours, and then rock asphalt powder, graphene and nano calcium carbonate powder are added thereto, and the mixture is quickly stirred and sealed to obtain the fast gelling agent.
4. The method for preparing the rapid gelling agent according to claim 3, characterized in that: In step S1, the stirring speed of high-speed stirring is 3000-5000r / min, and the stirring time is 25-35min; in step S2, the stirring speed of stirring is 1500-2500r / min, and the stirring time is 25-35min; in step S3, the stirring speed of rapid stirring is 2000-4000r / min, and the stirring time is 15-25min.
5. Use of the fast gelling agent as claimed in claim 1 or 2 in the closed construction of ballasted track subgrade.
6. The use of the fast gelling agent according to claim 5 in the closed construction of ballasted track subgrade, characterized in that: The fast gel coagulant and graded crushed stone are used at room temperature to quickly spray the sealing material from the line through the material pipe to the surface of the roadbed, and artificially laid fast gel coagulant anti-seepage stickers are formed on the ballasted track roadbed to form an organic flexible polymer consolidation layer. The addition amount of the fast gel coagulant accounts for 9-12% of the weight of the graded crushed stone. The maximum particle size of the graded crushed stone is 13.2mm, and the nominal maximum particle size is 9.5mm. The fast gel coagulant anti-seepage sticker is made of the fast gel coagulant and glass fiber, and has a thickness of 2-3mm.
7. The use of the fast gelling agent according to claim 6 in the closed construction of ballasted track subgrade, characterized in that: The grading range of the graded crushed stone is: particle size <0.075mm accounts for 4.2-7.2%, particle size <0.15mm accounts for 6.8-14.8%, particle size <0.3mm accounts for 9.8-20.6%, particle size <0.6mm accounts for 13.6-29.5%, particle size <1.18mm accounts for 22.7-40.6%, particle size <2.36mm accounts for 32.1-55.2%, particle size <4.75mm accounts for 52.7-74.6%, particle size <9.5mm accounts for 92.6-97.8%, and particle size <13.2mm accounts for 100%.
8. The use of the fast gelling agent according to claim 7 in the closed construction of ballasted track subgrade, characterized in that: The grading range of the graded crushed stone is as follows: particle size <0.075mm accounts for 7.2%, particle size <0.15mm accounts for 14.8%, particle size <0.3mm accounts for 20.6%, particle size <0.6mm accounts for 29.5%, particle size <1.18mm accounts for 40.6%, particle size <2.36mm accounts for 55.2%, particle size <4.75mm accounts for 74.6%, particle size <9.5mm accounts for 97.8%, and particle size <13.2mm accounts for 100%; the added amount of the fast gelling agent accounts for 9.5% of the weight of the graded crushed stone.
9. The use of the fast gelling agent according to claim 6 in the closed construction of ballasted track subgrade, characterized in that: The thickness of the organic flexible polymer consolidation layer is 3-5 cm.